An Experimental Study on Production of Egg Yolk Antibody(IgY) against Bee Venom - Hwang, Tae-Jun; Lee, Seung-Bae; Gwon, Gi-Rok (Journal of Pharmacopuncture, 2001)
This study was carried out for production of neutral antibody to bee venom(anti-phospholipase A2 IgY). Hen layings were injected repeatedly with bee venom and phospholipase A2 with Freund's adjuvant. Specific antibody in egg yolk from immunized hen laying was separated, and purified, also immunological characteristics of anti-phospholipase A2 IgY was invested. The results were summarized as follows : 1. Phospholipase A2 was showed single band at molecular weight 17,000 in SDS-PAGE and bee venom was showed two band at molecular weight 17,000 and under molecular weight 6,500 in SDS-PAGE. 2. During 70 days after hen immunized with bee venom and phospholipase A2, antibodies(anti-bee venom IgY) to bee venom were showed poor ELISA value in egg yolk, but antibodies(anti-Phospholipase A2 IgY) to phospholipase A2 in egg yolk were increased ELISA value from 8 days or 15 days and found maximum ELISA value at 42 days. Also after booster at 49 days, ELISA value of anti-Phospholipase A2 IgY in egg yolk was supported at optical density(O.D) 1.0 level, continuously. 3. Titer of phospholipase A2 IgY was showed 1: 32,000. 4. In double immunodiffusion test to phospholipase A2 after double dilution of anti-phospholipase A2 IgY, only precipitation line was made in 1:1 dilution well of anti-Phospholipase A2 IgY. But In immunodiffusion test to anti-phospholipase A2 IgY after double dilution of phospholipase A2, Precipitation line to 250ul/ml well of phospholipase A2 was showed. In double immunodiffusion test to bee venom(1mg/ml) after double dilution anti-phospholipase A2 IgY, all well without 1:32 dilution well were showed strong precipitation line. 5. In dot bloting test to anti-phospholipase A2 IgY after diluting bee venom(0.5mg/ml), dot bloting color was showed clearly to 1/100(5㎍/㎖) in bee venom.